Breast Cancer Survival in Eastern Region of Ghana - Ssentongo, Paddy; Oh, John S.; Amponsah-Manu, Forster; Wong, William; Candela, Xavier; Acharya, Yubraj; Ssentongo, Anna E.; Dodge, Daleela G. (Frontiers in Public Health, 2022)
Objective Five-year overall survival rate of breast cancer in low-income countries (LICs) is significantly lower than in high-resource countries. This study explored clinical and pathological factors influencing mortality in the Eastern region of Ghana. Methods We performed a retrospective medical chart review for patients undergoing surgery and chemotherapy for breast cancer at a regional hospital in Ghana from January 2014 to January 2017. Descriptive and survival analysis was done. Results One hundred and twenty-nine patients were included in the study. The median age at presentation was 51 years. Sixty percent of patients presented with poorly differential histological grade III. The most common histological type was invasive ductal carcinoma (83%). Based on stage assessment using only tumor size and lymph node status, 60% presented at stage 3. Only 25% were tested for hormone receptor proteins and HER2 status. Of these, 57% had triple-negative breast cancer (TNBC). The 3-year overall survival rate was only 52%. Conclusion The cumulative 3-year survival was 52%. Despite success in reducing cancer mortality in northern Africa, survival in sub-Saharan Africa remains poor. A significantly higher percentage of GIII and TNBC is found in breast cancers seen in Ghana. When combined with limited capacity for accurate diagnosis, cancer subtype analysis, adequate therapy, and follow-up, late-stage presentation leads to poor outcomes. Future studies should emphasize the identification of barriers to care and opportunities for cost-effective and sustainable improvements in diagnosing and treating breast cancer in LICs.